Perlakuan Dengan Pendekatan Pembelajaran Melalui Metode Bermain Peran Bagi Siswa Yang Sulit Berinteraksi - Rukli; Andi Andry Tenriana (CV Edujavare Publishing, 2024)
This research was conducted based on the findings of problems related to students' social interaction abilities in class II of SDN No. 198 Inpres Bontorita. These problems are students who have a tendency to play alone, lack of social interaction, do not greet each other, rarely make eye contact when conversing, and often use Student Activity Sheets (LKS) during the learning process. The aim of this research is to obtain an overview of the application of a learning approach through role playing methods in improving the social interaction abilities of class II students at SDN No. 198 Inpres Bontorita. This research uses classroom action research methods. The subjects in this research were 13 students consisting of 5 male students and 8 female students. The results of the research show that the achievement of students' social interaction skills has increased in each indicator, including students being able to greet, students being able to communicate verbally, students being able to ask for help, students being able to listen, students being able to ask questions and students being able to carry on a conversation.